Corporate Social Disclosures and Financial Performance of Quoted Oil and Gas Companies in Nigeria - Saturday Hope Enwien; Ebiaghan Frank Orits (Review of Ethics in Sustainable Finance and Accounting, 2025)
This study examined the extent to which corporate social responsibility (CSR) disclosures impact the financial performance of publicly quoted oil and gas companies in Nigeria. Two CSR disclosure indicators - local community initiatives and social donations/gifting - were employed as independent variables, alongside four financial performance indicators: return on assets (ROA), return on equity (ROE), return on capital employed (ROCE), and earnings per share (EPS). Firm size served as a control variable. Using dummy variables for CSR disclosures and panel data from 10 companies over a 10-year period (2014–2023), the analysis applied descriptive, post-estimation, and inferential statistics through fixed and random effects models.Findings revealed that CSR disclosures significantly influenced ROA (F = 11.31; p < 0.05), ROCE (F = 9.54; p < 0.05), and EPS (F = 32.40; p < 0.05), while their effect on ROE was insignificant (F = 1.26; p = 0.2933 > 0.05). The study concludes that CSR disclosures are key determinants of financial performance, particularly in enhancing ROA, ROCE, and EPS.Based on the findings, it is recommended that regulatory authorities in Nigeria’s oil and gas sector encourage firms to invest more in CSR-related ventures, as they have proven financial benefits. Furthermore, oil and gas companies should scale up in size and capital employed while advocating for greater CSR transparency to enhance overall financial performance.